Development of a pulse oximeter. - Pérez Casillas, L. M. (Revista Mexicana de Ingenieria Biomedica, 1988)
A pulse oximeter was designed to analyze the oxygen saturation of the arterial blood, which can be determined in several points of the body from the difference of observation of red and infrared light by the different hemoglobin species depending on the a logarithmic processing, which separates the pulsatile components that allow the measurement of this parameter in a continuous and non-invasive way. This is an "in vitro" development being tested at the Angeles del Pedregal hospital. The calibration tests show a repeatability of 92.3%.